Analysis of the Pronunciation of Iqra' in QS. Al-'Alaq Verse 1 through the Rules of Insya' Talab Amr and Its Implications in Islamic Da'wah Methods - Nurin Alfiani Nurin; Muhammad Arwani Rofi’i; Fuji Lestari (Fakultas Dakwah UIN KHAS Jember, 2025)
The word iqra' in QS. Al-'Alaq verse 1 is one of the words that is interesting to study. Why the word iqra' became the first revelation revealed to the Prophet Muhammad SAW, who was ummi, and the ambiguity of the object that must be read, raises profound questions about the hidden meaning in that word. This study aims to reveal the deeper meaning of the word iqra' through the kaidah insya' talab amr in the science of ma'ani Al-Qur'an, and its implications in Islamic da'wah methods. This study uses the library research method with an approach based on the science of ma'ani Al-Qur'an. The results of the study show that the rule of insya' talab amr requires the implementation of a task by a higher party to a lower party. The phrase iqra' in the Qur'an is mentioned 16 times in 8 surahs with different derivations, which shows the importance of this command in various contexts. The word iqra' (read) is a form of fiil amr which, in the study of ma'ani science, is included in the insya' talab rule, which demands that something be done. In addition to the literal meaning of